Characteristics of the Construction Industry from the Marketing Viewpoint: Challenges and Solutions - Mahmood Mokhtariani; Mohammad Hassan Sebt; Hamid Davoudpour (Salehan Institute of Higher Education, 2017)
Marketing management plays a crucial role in successful companies. However, marketing has been either misunderstood or entirely neglected in numerous construction companies because it is difficult to apply conventional marketing strategies due to specific characteristics of the industry. This study systematically investigates the characteristics of the construction industry and their effects on marketing management. A systematic literature review covering scientific papers from 1995 to 2015 (556 scientific papers) identifies 16 characteristics, which are organized into two main categories—the construction industry and construction product-related industry. 'Fragmentation' was the most highlighted characteristic.A total of 10 identified characteristics, according to the experts' opinions gathered through the questionnaire, may affect the construction marketing, of which